Synteny-based analyses indicate that sequence divergence is not the main source of orphan genes - Mc Lysaght, Aoife (My University, 2020)
The origin of ‘orphan’ genes, species-specific sequences that lack detectable homologues, has remained mysterious since the dawn of the genomic era. There are two dominant explanations for orphan genes: complete sequence divergence from ancestral genes, such that homologues are not readily detectable; and de novo emergence from ancestral non-genic sequences, such that homologues genuinely do not exist. The relative contribution of the two processes remains unknown. Here, we harness the special circumstance of conserved synteny to estimate the contribution of complete divergence to the pool of orphan genes. By separately comparing yeast, fly and human genes to related taxa using conservative criteria, we find that complete divergence accounts, on average, for at most a third of eukaryotic orphan and taxonomically restricted genes. We observe that complete divergence occurs at a stable rate within a phylum but at different rates between phyla, and is frequently associated with gene shortening akin to pseudogenization.
PUBLISHED
Keywords: D. melanogaster; S. cerevisiae; Computational biology; Conserved synteny; De novo gene emergence; Evolution; Evolutionary biology; Genetic novelty; Human; Orphan genes; Sequence divergence; Systems biology